MORPHOLOGICAL AND MOLECULAR VARIABILITY IN ISOLATES OF Alternaria lternaria Spp. CAUSING LEAF BLIGHT OF COTTON - S. A. ASHTAPUTRE; V. R. KULKARNI (The Bioscan, 2018)
Leaf blight of cotton caused by Alternaria spp is an important disease and the samples were collected during the survey for the study of morphological and molecular variability. The study of variability with respect to morphological characters revealed that out of 25 isolates of Alternaria spp, 18 isolates showed complete resemblance with Alternaria macrospora and remaining 7 isolates resembles to Alternaria alternata. The conidial size varied from 42.43 x17.69 ìm in Garag and 76.20x13.20 ìm Tadakod isolates. The molecular variability study revealed that the DNA sequences of twenty five isolates were compared using the bioinformatics tool of the National Centre for Bioinformatics (NCBI) blast programme. Based on sequence comparison, the identification of Alternaria spp. isolates was confirmed and all the sequences of isolates were confirmed as eighteen isolates Alternaria macrospora, and seven as Alternaria alternata and accordingly phylogenetic trees were constructed. The present investigation revealed that there is greater morphological and molecular variability among the different isolates of Alternaria sp. It also shows that the genetic variation among the pathogen varies from location to location.